Pengaruh Experiental Marketing Dan Brand Trust Terhadap Loyalitas Nasabah Dengan Kepuasan Nasabah Sebagai Variabel Intervening - Sindi Sihombing; Zuhrinal M Nawawi; Atika Atika (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This research aims to determine the influence of Experintal Marketing and Brand Trust on consumer loyalty with consumer satisfaction as an intervening variable, the external variables used in this research are Experintal Marketing and Brand Trust, while the intervening variables in this research are consumer satisfaction and the endogenous variables in this research customer loyalty, this research was conducted at Bank Syariah Indonesia Kcp Simpang Limun, the data collection method was carried out through distributing questionnaires, data analysis techniques used descriptive analysis and path analysis, the path results showed that the variables Experintal Marketing and Brand Trust had a significant effect on customer satisfaction of 22,760 %. and the Brand Trust variable has a significant influence on consumer satisfaction of 8.589%. The total influence of the variables Experintal Marketing and Brand Trust, and consumer satisfaction on consumer loyalty has an effect of 1.1025%. The Experimental Marketing variable has no direct effect on consumer loyalty at 6.93%, while the consumer satisfaction variable has a significant effect on consumer loyalty at 1.1025%.